The science of free will bridging theory and positive psychology - Baumeister, Roy F. 1953- (Oxford University Press, 2024)
"At first blush, free will seems obvious. Every day, people have the experience of making decisions, of choosing what to do. Planning a meeting or date, steering a car, ordering from a menu, accepting or declining an offer, playing a game, making a deal, voting, shopping, and much more -- all these confront the person with multiple alternative possibilities. People make choices, fully aware that they could just as well choose differently."
Keywords: Entscheidungsfindung; Bewusstsein; Willensfreiheit; Free will and determinism; Choice (Psychology)